EFFECTS OF A MOOD INDUCTION PROCEDURE IN WORDS RECALL BIASES - Blasco, Tomás; Borràs, F. Xavier; Rey, Marta; Bonillo, Albert; Fernández Castro, Jordi (Anales de Psicología / Annals of Psychology)
Standardized mood induction procedures in laboratory settings have been widely used to investigate relationships between mood states, cognitions and behaviors. The aim of this study was to examine in our cultural scene the efficacy of viewing films with emotional contents as a single procedure to induce mood states, as well as to assess their effects in words recall. Mood states using two questionnaires (POMS and IDDA-EA) and recall of words with positive and negative affect meaning, were assessed in 119 studens before and after viewing a "happy" or a "sad" film. Significant statistical changes were observed in all POMS subscales as well as in the "Activation" and "Stress" subscales of the IDDA-EA. Furthermore, an increase in the recalling of words with positive affect meaning was observed in the group that saw the "happy" film. These results seem to indicate that the procedure is adequate to induce mood changes in laboratory settings. On the other hand, some manipulations addressed to enhance the efficacy of this mood induction procedure are suggested.